Book Review - Garton Ash, Timothy; Fussell, Paul; Unterberger, Betty Miller; Seiffert, Wolfgang; Stern, Robert M.; Sachs, Jeffrey D.; Adams, William James; Wilmsen, Edwin N.; Dinstein, Yoram; McKibben, Bill; Peterson, Dale; Jervis, Robert; Seale, Patrick; Canack, William L.; Ryback, Timothy W.; Perry, Mark; Goldston, James A.; Garton Ash, Timothy; Fussell, Paul; Hixson, Walter L.; Bress, Albert; Nicolaidis, Kalypso; Ambrosius, G.; Hubbard, William (Tufts Archival Research Center, 2005)
Volume 14, Issue 2. Summer. The Uses of Adversity: Essays on the Fate of Central Europe. Wartime: Understanding and Behavior in the Second World War. The United States, Revolutionary Russia, and the Rise of Czechoslovakia. Die Deutschen und Gorbatschow: Chancen fir einen Interessenausgleich. Trade and Investment Relations among the United States, Canada, and Japan. Developing Country Debt and the World Economy. Restructuring the French Economy. Land Filled with Flies. International Law at a Time of Perplexity: Essays in Honor of Shabtai Rosenne. The End of Nature. The Deluge and the Ark. The Meaning of Nuclear Revolution: Statecraft and the Prospect of Armageddon. Asad of Syria: The Struggle for the Middle East. Lost Promises: Debt, Austerity and Development in Latin America. Rock Around the Bloc: A History of Rock Music in Eastern Europe and the Soviet Union . Four Stars. Shattered Hope: Guatemalan Workers and the Promise of Democracy. George F. Kennan: Cold War Iconoclast. Strategic Trends in Services: An Inquiry into the Global Services Economy . A Social and Economic History of 20th Century Europe. Book Review